Best archival practice in the regulation of medicines: work on the guidelines for agencies for medicinal products - Rajh, Arian; Stančić, Hrvoje (2011)
This paper announces the beginning of the work on the standardization of filing of electronic medicinal dossiers in agencies for medicinal products. Medicinal products electronic dossiers have to be preserved for the long-term because of the requirements for protection of patients’ safety and standardization of ar¬chiving procedures.
Projekt MZOS
ENG